Prosthetic treatment with overdenture in an elderly - Yurima Trupman Hernández; Luisa Limonta Bandera; Marcia Hortensia Corona Carpio (Centro Provincial de Información de Ciencias Médicas, 2022)
The case report of a half blood 63 years elderly with good general health, who visited the Dental Prosthesis Service in the Mártires del Moncada Teaching Provincial Estomatological Clinic in Santiago de Cuba is described, as he was esthetically affected and, he wished to preserve his remanent teeth; he informed that he had not received any previous prosthetic treatment. After making oral and dental exploration and other exams, as well as other odontological procedures, it was decided to rehabilitate him with overdentures to preserve the abutment teeth, to reestablish the lost functions and to improve esthetics. The patient was rehabilitated esthetically and functionally and he showed a satisfactory clinical course.